The association between resting heart rate and HbA1c-assessed glycemic control in patients with type 2 diabetes in Eastern China - Chen, Xiangyu; Lu, Feng; Zhang, Jie; Du, Xiaofu; Xu, Chunxiao; Liang, Mingbin; Chen, Lijin; Zhong, Jieming (Frontiers in Endocrinology, 2025)
ObjectivesThis study aimed to explore the association between resting heart rate (RHR) and HbA1c-assessed glycemic control in patients with type 2 diabetes mellitus (T2DM).MethodsThis cross-sectional study was conducted in Zhejiang Province, Eastern China, from March to November 2018. The association between RHR and inadequate glycemic control was analyzed using multivariable logistic regression and restricted cubic spline models. Additionally, a generalized additive model was employed to examine the association between RHR and HbA1c levels.ResultsA total of 1,756 patients with T2DM were included in this study. The prevalence of inadequate glycemic control was 48.92% in this population. After adjusting for age, sex, educational level, body mass index, hypertension, abnormal total cholesterol, abnormal triglyceride, cigarette smoking, and duration of diabetes, when compared to the first quintile of RHR (< 70 beats per minute [bpm]), patients in the second quintile (70–75 bpm), third quintile (76–80 bpm), fourth quintile (81–87 bpm), and fifth quintile (≥88 bpm) had increased risks of inadequate glycemic control, the adjusted odds ratios (ORs) with 95% confidence intervals (CIs) were: 1.11 (0.82-1.49), 1.50 (1.10-2.06), 1.70 (1.25-2.31), and 2.14 (1.56-2.94), respectively. When RHR was treated as a continuous variable, each 10 bpm increase was associated with a 27% higher risk of inadequate glycemic control (OR: 1.27; 95% CI: 1.16-1.39). Moreover, HbA1c levels were positively correlated with increasing RHR in this population (Spearman correlation coefficient=0.15, P<0.001). Subgroup analyses confirmed that the association between elevated RHR and inadequate glycemic control persisted across all key demographic strata (all p < 0.05). Notably, BMI significantly modified this relationship (p for interaction < 0.05), with a more pronounced effect observed in individuals with higher BMI.ConclusionsElevated RHR is associated with inadequate glycemic control and higher HbA1c levels. Our findings suggest a potential bidirectional relationship between RHR and glycemic control in T2DM patients. These results may contribute to individualized clinical management and inform targeted public health strategies aimed at early identification and intervention in high-risk T2DM populations.